Effect of Different Etching Modes on Shear Bond Strength of Universal Adhesives to Enamel - Haider, Nida; Nagpal, Rajni; Singh, Udai Pratap; Umar, Madeha; Mehmood, Nida (The Journal of Dentists, 2021)
Aim: To evaluate the effect of different etching modes on the bonding efficacy of two universal adhesives to enamel. Materials and method: The study was performed in fifty five extracted human molar teeth. For shear bond strength testing, flat buccal surfaces were prepared. Teeth were randomly divided into five experimental groups according to two universal adhesives Single Bond Universal (3M ESPE, U.S.A) and Tetric N-Bond Universal (IvoclarVivadent) used in different etching modes i.e etch-and-rinse and self-etch mode and one control group of etch & rinse adhesive (Adper Single bond-2). Teeth were mounted in self-cure acrylic resin and composite restorations were placed in all the samples after application of adhesives according to the manufacturer’s instructions. Ten samples from each group were subjected to shear bond strength evaluation. Additionally one sample per group was subjected to scanning electron microscopic analysis for observing resin-enamel interfacial adaptation. Statistical analysis: Data collected was subjected to statistical analysis using one –way ANOVA and post-hoc tukey’s test at a significant level of p<0.05. Results: Enamel bond strength was significantly better in etch-and-rinse mode than the self etch mode for both Single Bond Universal (gp 2 & 3; p=0.017) and Tetric N-Bond Universal adhesives (gp 4 & 5; p=0.046) respectively. Conclusion: Phosphoric acid etching of enamel prior to the application of a mild universal adhesive is an advisable strategy for optimizing bonding.